Prototype development of web services based on web service-oriented architectures / Norbaitee Arshad - Arshad, Norbaitee (Faculty of Computer and Mathematical Sciences, 2007)
Web service is the new technology that apply the techniques to reduce the time and cost of web application development. It uses the Service-oriented Architectures (SOA) as the basic architecture for web service development. Web service can be applied to many other technologies such as console application, mobile technology, window based application etc. This research focuses on the development of prototype of web services based on web service oriented architecture. It also involves the building the interaction between the elements of SOA architecture. This paper uses data from ILMU database provided by Perpustakaan Tun Abdul Razak (PTAR) and the dummy database. The scope focuses on the service to retrieve the reference information. The development of web service involves the several stages. The Java lanpiiage is used as the application language and the interface. The development tool is NetBeans IDE 5.5. The input parameter will be produced by the user in term keyword text. Keyword: Web service. Service-oriented Architectures (SOA), middleware, search engine, service-orientation